Building Community Participation in the Development of Warloka Pesisir Village as a Modern Fishing Village in West Manggarai - Adiyatma Rakhmawati; Atika Wijaya (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
Community participation is essential in developing tourism villages because the potential of social and cultural diversity resources in the community is the primary driving force behind the activities in the tourism village. This research aims to analyze the stages and obstacles of community participation in the development of Warloka Pesisir Tourism Village. This research uses qualitative research with descriptive research type. Data were gathered using observation, interviews, focus group discussion impacts (FGDs), and documentation. The concept used to analyze the data is the concept of participation from Cohen and Uphoff. The results showed that based on the four types of participation, the Warloka Pesisir community has not yet reached an optimal level of participation in developing a tourism village. Participation in decision-making and benefit-taking shows that the community is passive in decision-making and tends only to follow the final decision. This has an impact on the community's lack of maximum benefits from the development of tourist villages. Some existing obstacles hinder participation and tourism development, so more attention must be paid to supporting community participation by updating infrastructure and developing skills with empowerment.